Mechanical properties of double and triple fibre-reinforced epoxy hybrid composites - BOZTOPRAK, YALÇIN (ICE PUBLISHING, 2020)
A composite material can be defined as a combination of two or more materials that provide better properties than the material used alone. Composite materials can be preferred because of their many advantages - for example, they are stronger and lighter compared with conventional materials. Usage of fibre-reinforced composite structures has increased in industries such as automotive, marine transportation, civil engineering, sporting goods, medical equipment and prosthetic devices.
Keywords: composites; hybrid materials; mechanical properties; POLYESTER; POLYAMIDE